Interconnections : Bridges, Routers, Switches and Internetworking Protocols, Second Edition - Perlman, Radia (Addison-Wesley Professional, 1999)
Radia Perlman's Interconnections is recognized as a leading text on networking theory and practice. It provides authoritative and comprehensive information on general networking concepts, routing algorithms and protocols, addressing, and the mechanics of bridges, routers, switches, and hubs. This Second Edition is expanded and updated to cover the newest developments in the field, including advances in switching and bridge technology, VLANs, Fast Ethernet, DHCP, ATM, and IPv6. Additional new topics include IPX, AppleTalk, and DECnet. You will gain a deeper understanding of the range of solutions possible and find valuable information on protocols for which documentation is not readily available elsewhere. Written by the inventor of many of the algorithms that make switching and routing robust and efficient, Interconnections, Second Edition offers an expert's insight into how and why networks operate as they do. Perlman describes all of the major networking algorithms and protocols in use today in clear and concise terms, while exploring the engineering trade-offs that the different approaches represent. The book contains extensive coverage of such topics as: The spanning tree algorithm The differences between bridges, routers, and switches Virtual LANs (VLANs) and Fast Ethernet Addressing and packet formats for IP, IPv6, IPX, CLNP, AppleTalk, and DECnet Autoconfiguration of addresses; strategies in various protocol suites Routing protocols, including RIP, IS-IS, OSPF, PNNI, NLSP, and BGP Layer 3 multicast protocols, including IGMP, DVMRP, MOSPF, CBT, PIM, BGMP, Simple Multicast, and Express Sabotage-proof routing Protocol design folklore 0201634481B04062001.